DEVELOPMENT OF PROBLEM BASED LEARNING TOOLS TO IMPROVE MATHEMATICS PROBLEM-SOLVING ABILITY - Beni Ardi; Mukhtar Mukhtar; Waminton Rajagukguk (SENSEI RESEARCH CENTER, 2021)
This research is the development of problem-based learning tools to improve the mathematical problem-solving abilities of students of SMP Private Bakti Medan class VIII for the 2021/2022 academic year. Effectiveness; 2) The mathematical problem-solving ability of students using learning tools with Problem Based Learning increased in terms of the average posttest value of the first trial was 76.88 increased to 81.19 in the second trial and experienced an increase in the distribution stage of 84.38 and the N-Gain of trial I was 0.31 in the medium category increased to 0.33 in the medium category in the second trial and at the distribution stage increased to 0, 42 medium categories. The learning tools developed in this research are the Student Book and LKPD. Device development is carried out using the four D model development model